Beyond Philanthropy: Can Waqf Be Indonesia's Key to Sustainable Development? - Ken Paramitha Aryana; Hasan, Annisa (CV Putra Publisher, 2026)
This study examines the strategic and multi-dimensional role of waqf in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia. With a significant financing gap hindering the realization of the SDGs, this research explores how waqf, a unique Islamic philanthropic instrument, can serve as a vital non-conventional funding source. Employing a qualitative approach and a literature review method, the study synthesizes scholarly articles, official reports, and historical data to build a comprehensive argument. The findings reveal a strong synergy between the principles of waqf and the 17 SDGs. The perpetual and productive nature of waqf assets allows for long-term, sustainable impact across social, economic, and environmental sectors. Case studies demonstrate waqf's direct contributions, from funding healthcare and education (SDGs 3 & 4) to empowering communities and promoting environmental conservation (SDGs 5, 14 & 15). However, the full potential of waqf remains largely untapped due to challenges in public literacy and institutional governance. The study concludes that optimizing waqf through integrated regulations, technological adoption, and innovative financing models is crucial for bridging the financing gap and advancing Indonesia's sustainable development agenda.